Visual Grammar and Intersemiotic Complementarity in BIPA Textbooks: A Multimodal Analysis of Sahabatku Indonesia - Tito Dimas Atmawijaya; Harni Kartika Ningsih; Bernadette Kushartanti (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
This study examines the state-funded BIPA textbooks by applying Kress and van Leeuwen's (2021) visual grammar and Unsworth's (2006) typology of intersemiosis patterns to identify how verbal and visual modes construct curricular objectives and instructions. The dataset comprised the Sahabatku Indonesia Level 1 and Level 2 textbooks, published by the Indonesian Ministry of Education and Culture for novice and elementary foreign learners of Indonesian. The analysis was conducted in two stages. It firstly mapped verbal and visual elements according to their pedagogical roles across 20 units (10 per level). It then categorized their relationships as interrelated, complementary, or integrated. Findings reveal that interrelated relations dominate peripheral sections (cover, pre-activity, cultural insight), while integrated relations characterise core instructional sections where visual and verbal modes are functionally interdependent. Across levels, visual density decreases and modality shifts from cartoon-style illustrations toward realistic photographs, reflecting systematic scaffolding withdrawal. However, writing sections lack adequate multimodal scaffolding for modelling and joint construction. The study demonstrates that the multimodal design of the Sahabatku Indonesia series is systematically structured yet unevenly realised across language skills, with writing sections requiring the most significant compositional improvement.